Can Islamic finance enhance the innovation capacity of Cameroonian SMEs? Empirical evidence based on a multivariate probit approach - Ali Haruna; Honoré Tekam Oumbé; Armand Mboutchouang Kountchou; Charles Bertin Pilag Kakeu (Borsa İstanbul Review, 2024)
This study examines the effects of the Islamic mode of financing on the innovation capacity of SMEs in Cameroon using a sample of 1358 SMEs. Results of the multivariate probit model indicate that Islamic finance enhances process innovation, product innovation, and marketing innovation. While the effects on organizational innovation are positive, they are statistically insignificant. Our main results equally indicate that the effects of Islamic finance on the innovation capacity of SMEs are more pronounced on technological innovation (process and product) than non-technological innovation (marketing and organizational). Policymakers are encouraged to put in place the necessary mechanisms for the promotion of Islamic finance such as the enacting of laws that ensure the creation of full-fledged Islamic banks, and raising awareness about the benefits and specificities of this mode of finance for the financing of SME innovation.
Keywords: 330; Cameroon; Islamic finance; Innovation; SMEs